High Serum HCV RNA in Chronic Hepatitis C Patients Coinfected with HIV despite Successful Antiretroviral Therapy. Issue 6 (August 2016) - Barreiro, Pablo; Labarga, Pablo; de Mendoza, Carmen; Benítez-Gutiérrez, Laura; Fernandez-Montero, José V; Peña, José M; Soriano, Vicente
Background: Baseline serum HCV RNA predicts treatment success in chronic hepatitis C patients. Thresholds at 0.8, 2, 4 and 6 million IU/ml discriminate treatment outcomes using distinct antiviral regimens. Compared to the general population, immunosuppressed individuals exhibit greater viral load values. This has been confirmed in HIV– HCV-coinfected patients, although little is known about the influence of antiretroviral therapy. Methods: Serum HCV RNA results recorded from all chronic hepatitis C patients who consecutively attended at our clinic were analysed. Results: A total of 813 patients with detectable HCV RNA were identified. HIV coinfection was present in 78.7%, of whom 91% were on antiretroviral therapy. Overall, 467 (57%), 273 (34%), 170 (21%) and 127 (16%) had HCV RNA >0.8, >2, >4 and >6 million IU/ml, respectively. These high viral load values were found in 60%/36%/23%/18% of HIV-positive versus 47%/25%/11%/6% of HIV-negative individuals ( P ≤0.01), respectively. In multivariate analysis, the greatest HCV RNA values were only significantly associated with HIV coinfection and HCV genotypes-1 or -4. Greater HCV RNA values were paradoxically found in HIV patients on than off antiretroviral therapy. Conclusions: Serum HCV RNA values above 0.8, 2, 4 and 6 million IU/ml are roughly seen in 47%, 25%, 11% and 6% of chronic hepatitis C monoinfected patients, respectively. Despite being on antiretroviral therapy, the corresponding figures are 1.3- to 3.0-fold greater in HIV–HCV-coinfected patients, who may benefit less frequently from shorter oral HCV treatment lengths.